Pulmonary Embolism in Patients with COVID-19: Comparison between Different Care Settings - Buso, Giacomo; Mazzolai, Lucia; Rueda-Camino, José Antonio; Fernández-Capitán, Carmen; Jiménez, David; Bikdeli, Behnood; Lobo, José Luis; Fernández-Reyes, José Luis; Ciammaichella, Maurizio; Monreal, Manuel; the RIETE Investigators (Seminars in Thrombosis and Hemostasis, 2021)
The clinical characteristics and outcomes of patients with coronavirus disease 2019 (COVID-19) who develop pulmonary embolism (PE) in the full spectrum of patient care settings need to be elucidated. The aim of this study was to compare the clinical characteristics, treatment, and 90-day outcomes in patients diagnosed with PE while recovering from COVID-19 in the outpatient setting versus those who were diagnosed with PE while being hospitalized with COVID-19. Data from the international Registro Informatizado de Enfermedad TromboEmbólica (RIETE) registry were used. The major study outcomes were all-cause death, major bleeding, and venous thromboembolism (VTE) recurrences during the first 90 days after PE. From March 2020 to March 2021, 737 patients with COVID-19 experienced acute PE. Of these, 340 (46%) were recovering from COVID-19 as outpatients (267 patients who had been treated at home for COVID-19 and 73 discharged after being hospitalized with COVID-19). Compared with inpatients with COVID-19, those recovering in the outpatient setting upon PE were less likely to be men (odds ratio [OR]: 0.54; 95% confidence interval [CI]: 0.40–0.72) and less likely to have hypertension (OR: 0.55; 95% CI: 0.41–0.74) or diabetes (OR: 0.51; 95% CI: 0.33–0.76). At 90-day follow-up, eight patients (none recovering from COVID-19 as outpatient vs. 2.4% of inpatients with COVID-19) developed recurrent VTE, 34 (1.9 vs. 7.9%) had major bleeding, and 128 (10 vs. 24%) died. On multivariable analysis, inpatients with COVID-19 were at a higher risk of major bleeding (adjusted hazard ratio [HR]: 6.80; 95% CI: 1.52–30.4) or death (adjusted HR: 2.24; 95% CI: 1.40–3.58). In conclusion, using a large multinational registry of patients with COVID-19 who experienced PE, thromboembolic episodes occurring in those recovering from COVID-19 as outpatients were associated with less ominous outcomes than inpatients with COVID-19.
Keywords: COVID-19; pulmonary embolism; outpatient; RIETE registry